From supply to demand chain management: efficiency and customer satisfaction - Heikkilä, Jussi (Journal of Operations Management, 2002)
AbstractHow do companies in the fast‐growing industries achieve good customer satisfaction together with efficiency in supply chain management (SCM)? This inductive case study of six customer cases of Nokia Networks, one of the leading providers of mobile telecommunication technology, led to propositions exploring that question. Good relationship between the customer and the supplier contributes to reliable information flows, and reliable demand information flows in turn contribute to high efficiency—these are well‐researched issues also in other industry environments. But in a fast‐growing systems business such as mobile telecommunications industry, the supplier needs to be able to adapt its offering to a wide variety of customer situations and needs. Understanding the customer’s situation and need together with the right offering contributes to good co‐operation in improving the joint demand chain, which further leads to superior demand chain efficiency and high customer satisfaction.